Sufis’ Actions Against the Dutch in Aceh in The Late 19th and Early 20th Centuries - Fakhriati Fakhriati (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2012)
Sufis in Aceh, historically, had shown its real action in their daily life in relation to both vertical and horizontal. For vertical relations, the followers performed any Sufi practice leading them to their God. For horizontal relationship, they protected and defended their society and state by performing jihad against the Dutch as colonizers and infidels for them. There are at Ieast three factors influenced Sufis actions to be more attractive. First, the condition of Acehnese sultanate became weak. Second, the Dutch seemed eagerly to expand their colonial territory to Aceh. Third, the Acehnese had already kept in touch with other Muslims in Arabia since the Islam coming to this area. This article elaborates in detail on this matter by using primary sources from manuscripts and archives. Besides, secondary sources are also referred for comperation.